Analysis of Consumer Characteristics and Conditions of Mass Transit With The BTS (BUY THE SERVICE) Scheme on The Gresik-Lamongan Route BTS - Diah Mega Alfianti; Hani Teki Tjendani; Budi Witjaksana (Syntax Corporation Indonesia, 2025)
The transportation sector plays a vital role in supporting urban residents' daily activities and improving their quality of life. It encompasses two critical components: facilitating movement and physically relocating goods and passengers from one place to another. Public transportation systems are essential for enhancing urban mobility, reducing traffic congestion, and promoting environmental sustainability. This study focuses on analyzing the condition and service quality of the public transportation system operated under the Buy The Service (BTS) scheme on the Gresik-Lamongan route. The research employs a mixed-methods approach, combining primary data gathered through questionnaires distributed to passengers and field observations with secondary data obtained from the East Java Provincial Transportation Office, Gresik Regency Transportation Office, and Lamongan Regency Transportation Office. Using the Importance Performance Analysis (IPA) method, this study evaluates key service attributes to identify gaps between passenger expectations and actual service delivery. The findings reveal that the Transjatim Corridor IV route serves a 53-kilometer journey with an estimated travel time of 1 hour and 40 minutes. It operates with 14 buses and 1 spare fleet and is equipped with safety features such as seat belts, fire extinguishers, and glass-breaking hammers. The service is popular among various demographics, including students, workers, and tourists, due to its affordability, comfort, and strategic connectivity. However, certain service indicators, such as fleet availability, punctuality, and cleanliness, require improvements to better meet passenger expectations. This research highlights the importance of continuous evaluation and enhancement of public transportation services to achieve optimal satisfaction and operational efficiency. The results provide valuable insights for policymakers and transportation operators in designing strategies to improve the quality of mass transit services, ensuring they are safe, efficient, and accessible to all user groups.